Projekt BORIS - izhodišča za razvoj ocene poplavnega in potresnega tveganja na čezmejnih območjih - Babič, Anže (Ujma (Ljubljana), 2022)
The paper presents activities implemented in 2021 and the scope of the international project BORIS. The project is funded by Directorate-General for European Civil Protection and Humanitarian Aid Operations (DG ECHO) and coordinated by partners from Italy. In addition to Slovenian representatives (UL FGG), the project includes partners from Italy, Austria, Turkey, and Montenegro. The main part of the paper comprises a review of national approaches for seismic and flood risk assessment in countries that participate in the project. Available data, related limitations and solutions for developing a harmonised methodology for risk assessments of such natural hazards in cross-border areas are presented and analysed. Based on the comparative analysis, it follows that reconciling different interests and available data, and finding the lowest common denominator, is one of the most important challenges in developing a methodology for a crossborder multi-risk assessment.
Keywords: BORIS project; cross-border areas; čezmejna območja; earthquakes; floods; KRPAN; poplave; potresi; projekt BORIS; risk; tveganje